Interactions in online forums: a case study among first year undergraduate students - DeWitt, Dorothy; Alias, Norlidah; Siraj, Saedah; Zakaria, Abd Razak (Frontiers Media, 2014)
In online communities of learners, interactions are essential for building knowledge. Cognitive interactions assist the learning of concepts and principles, while social interactions engage and motivate learners. However in instructional activities,most of the time the acquisition of factual knowledge is stressed upon, and not the interactions. In this study, the online communications of students in their first semester of an undergraduate course, Computers in Counseling, were investigated to determine the types of interactions that took place during the online discussions, and whether these discussions contributed to knowledge-building.The30 undergraduate students participated in an online discussion forum, posting their responses to the questions given. Content analysis of the transcripts of their online communications was done to classify the types of interactions. This was followed by a survey of the students’ perceptions of discussion forums for learning. The findings showed that a large proportion of the interactions was cognitive interactions (46.0%), followed by attitudes (22.3%),social interactions(19.6%) and noise (5.3%). The students perceived that discussion forums were effective for collaborative learning (60.0%) and enabled ICT and communication skills (16.7% each), as well as self-regulated learning skills (13.3%) to be developed. The analysis of the open-ended responses indicated that it was perceived as useful for the construction of knowledge. This study is significant as it shows that interactions on online communication tools should be encouraged for collaboration and sharing of ideas for learning.